ANALISIS ARTIKEL TERKAIT FAKTOR-FAKTOR LOGISTIK YANG BERPERAN DALAM MENINGKATKAN MUTU KUALITAS PENGIRIMAN BARANG ATAUPUN PENGGUNAAN JASA - Muhammad Nanda Gymnastiar; Ariel L J Lumalesil; Elang Alifian Marvin; Siti Sahara (Cross-border, 2023)
This study aims to explore information related to logistical factors that play a role in improving the quality of the quality of delivery of goods or the use of services. The method taken in conducting this research is a descriptive qualitative research method, namely by looking for data in the form of article literature related to the research topic. From the analysis of several articles, the final results were obtained in the form of findings of several logistical elements supporting the maximum quality of delivery of goods or the use of services, such as the development of good coordination and communication, human focus, maximization of service services, appropriate decision making in capital management and punctuality.